Entre permanências e transformações: a morfologia urbana e a constituição espacial da região da Avenida Getúlio Vargas em Patos de Minas - MG - Elias, Júlia Tavares de Sousa (2023)
Since the 1970s, mid-sized cities play an important role in the contemporary Brazilian urban landscape, which allows the expansion of one’s ways of acting and thinking about the territories. Research on the processes of central regions’ landscape transformation is relevant within the new panorama, since these areas define the initial urban morphology of mid-sized cities. Thus, this study investigates the urban landscape transformation of Avenida Getúlio Vargas into Patos de Minas - MG, area of the original core and an important element of population identification. Composed, along with Praça Dom Eduardo, by ten blocks listed as Urban Environmental Heritage, has distinct characteristics in the landscape: significant and large afforestation, with European-inspired size and landscaping, local character, institutional axis and listed and inventoried buildings. The methodology covers bibliographic and documentary research, photographic assay, and morphological analysis. The study shows that mutations in the different phases of the avenue, in the horizontal and dense periods, do not interfere with its importance for the urban context. Therefore, the research aims to contribute to the planning and management of the urban landscape of Avenida Getúlio Vargas as a heritage of the city of Patos de Minas - MG and its inhabitants.